2022
DOI: 10.1128/spectrum.00851-22
|View full text |Cite
|
Sign up to set email alerts
|

Comparative In Vitro Study of Biofilm Formation and Antimicrobial Susceptibility in Gram-Negative Bacilli Isolated from Prosthetic Joint Infections

Abstract: This study is the first one to analyze a high number of isolates of Gram-negative bacilli that are the cause of prosthetic joint infection. The analysis includes biofilm development and antimicrobial susceptibility testing of both planktonic and sessile bacteria. The obtained results support the clinical knowledge about the treatment of these bacteria when biofilms are involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 46 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…Patients with IRIs caused by gram‐negative bacteria often have a worse prognosis than those with IRIs caused by gram‐positive bacteria, even after sufficient treatment. [ 16 ] The barrier effect of biofilms means that the direct effect of antibiotics is resisted. However, the cell membrane component of E. coli OMVs in HMLS increases the specificity of nanoparticles, as HMLS can be effectively internalized by bacteria, improving drug efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Patients with IRIs caused by gram‐negative bacteria often have a worse prognosis than those with IRIs caused by gram‐positive bacteria, even after sufficient treatment. [ 16 ] The barrier effect of biofilms means that the direct effect of antibiotics is resisted. However, the cell membrane component of E. coli OMVs in HMLS increases the specificity of nanoparticles, as HMLS can be effectively internalized by bacteria, improving drug efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…[27] reported that 35.2% were strong biofilm forming isolates, 16.7% were moderate biofilm forming and 27.8% were weak biofilm forming, the different methods used for assessment of the strength of biofilm formation could be a potential cause for this variation. Macias-Valcayo et al (2022) [24] also reported different results where 41.3% of their isolates were strong producers, 34.8% were moderate and 21.8% were weak biofilm-producers.…”
Section: Table (2) and Figure (4)mentioning
confidence: 96%
“…(Table 3) and (Figure 5). ---------------------------------------------------- [22] studies where (64.28%) and (62.73%) of isolates were biofilm forming, respectively, Baidya et al (2021) [23] reported biofilm-formation in 56.3% of their isolates, and Macias-Valcayo et al (2022) [24] reported that most of Gram negative strains of HAIs were biofilm producers (97%).The results of Almalki and Varghese (2020) [25] where different from our results where they reported that (63.9%) of isolates were non-biofilm forming while biofilm forming isolates were (36.1%), which could be attributed to the difference in the species of Gram negative isolates and the single potential of every pathogen to form biofilms.…”
Section: Table (2) and Figure (4)mentioning
confidence: 98%
“…This phenomenon is primarily responsible for the lack of therapeutic success with systemic antibiotics, since biofilm confers antimicrobial tolerance, reduces antibiotic diffusion and penetration, and evades the host immune response. Recently, it has been described that the extracellular matrix is one of the main factors responsible for resistance, in addition to other intrinsic factors specific to each strain that directly affect biofilm formation and cell dispersion [26][27][28][29][30][31].…”
Section: Question 5 What Are the Consequences Of Cri In Terms Of Morb...mentioning
confidence: 99%